2006
DOI: 10.1128/aem.72.4.2815-2823.2006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Intestinal Microbiota and Response to Dietary Virginiamycin Supplementation in the Broiler Chicken

Abstract: The inclusion of antibiotic growth promoters, such as virginiamycin, at subtherapeutic levels in poultry feeds has a positive effect on health and growth characteristics, possibly due to beneficial effects on the host gastrointestinal microbiota. To improve our understanding of the chicken gastrointestinal microbiota and the effect of virginiamycin on its composition, we characterized the bacteria found in five different gastrointestinal tract locations (duodenal loop, mid-jejunum, proximal ileum, ileocecal ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
124
1
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(146 citation statements)
references
References 42 publications
17
124
1
4
Order By: Relevance
“…A positive relation between the increase in abundance of Lactobacillus spp. population and an increase in weight gain has been shown in other animal models (18,21).…”
Section: Discussionmentioning
confidence: 99%
“…A positive relation between the increase in abundance of Lactobacillus spp. population and an increase in weight gain has been shown in other animal models (18,21).…”
Section: Discussionmentioning
confidence: 99%
“…There have been additional studies of the bacterial composition of the gut in other animals, including chickens (Dumonceaux et al, 2006), mice (Yap et al, 2008), pigs (Hill et al,8 2005), and cows (Hernandez et al, 2008). These studies have revealed that each animal species has a gut microbiota that is unique and representative of that species.…”
Section: Identification Of Microorganisms In the Gutmentioning
confidence: 99%
“…The number of LAB was not influenced by the pH value. There were many other factors affecting such as diet, age, presence of barrier in the intestine and different physiological functions within the organ system (Dumonceaux et al, 2006).…”
Section: Population Of Culturable Lab In Chicken Gastrointestinal Tractsmentioning
confidence: 99%